Chinese Herbal Medicine (Yiqi-Yangyin-Jiedu Decoction) Combined With Osimertinib as First-Line Treatment in EGFR Mutation-Positive Advanced Non-Small-Cell Lung Cancer (CATLA-2): A Study Protocol for a Double-Blind Randomized Controlled Trial - Yao, Jialin; Lu, Yan; Jiao, Lijing; Bi, Ling; Yang, Wenxiao; Su, Lingzi; Shi, Jun; Wang, Zhe; Gong, Yabin; Xu, Ling (Frontiers in Pharmacology, 2022)
Background: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR-TKIs) significantly improve the prognosis of non-small cell lung cancer (NSCLC) with EGFR mutation-positive. Although third-generation EGFR-TKI osimertinib is demonstrated with superior efficacy compared with first-generation EGFR-TKIs, acquired resistance to EGFR-TKIs remains the bottleneck. The Chinese herbal medicine (CHM) Yiqi-Yangyin-Jiedu decoction (YYJD) has been shown to delay acquired resistance to first-generation EGFR-TKIs in the CATLA study, but there is no high-level evidence for its effect when combined with osimertinib. This trial aims to evaluate the efficacy and safety of YYJD combined with osimertinib as first-line treatment in EGFR mutation-positive advanced NSCLC. Methods: This is a double-blind, multi-center, randomized controlled trial conducted in eight hospitals in China. A total of 314 participants will be randomly assigned to the osimertinib plus YYJD group (O+YYJD) or the osimertinib plus placebo group (O+placebo). Treatment will last until disease progression or death. Patients diagnosed with advanced NSCLC harboring EGFR Ex19del or L858R will be enrolled if they are ready to take osimertinib as first-line treatment, aged 18–74 years old, and provide signed informed consent. The primary outcome is progression-free survival (PFS). The secondary outcomes include a comparison of overall survival (OS), objective response rate (ORR), disease control rate (DCR), and quality of life (QoL). The analysis will be based on intention-to-treat and per-protocol subject analysis principles. Discussion: The goal of this trial is to evaluate the efficacy and safety of YYJD when added to osimertinib as first-line treatment in EGFR mutation-positive advanced NSCLC.